Performance and Egg Quality Characteristics of Egg-Type Chickens as Influenced by Fluted Pumpkin (Telfaria Occidentalis) Leaf Extract - Ladokun, A.o; Obe, A.A; Oso, A.O; Oke, O.E; Abiona, J.A (Nigerian Journal of Animal Science, 2023)
Atotal of 120 sixteen week old point of lay birds of the Isa Brown strain were used for the experiment to determine the effect of fluted pumpkin (Telfaria occidentalis) leaf extract (FPLE) administered orally on Laying performance, egg quality characteristics; blood chemistry haematology and serum chemistry for a 12 week period. The birds were randomly assigned to five treatment groups: control group with no FPLE; 30ml FPLE/litre of drinking water; 60ml FPLE; 90ml FPLE and 120ml/litre FPLE respectively at 3 day intervals. Feed was given ad libitum. Eggs were collected at 2 week interval to determine external and internal egg qualities. Blood sampling was carried out at the twelfth week of experiment. The results show that FPLE significantly (P<0.05) increased hen day with birds in group with 120ml FPLE/litre water having higher values than other groups. External egg qualities were not influenced by FPLE inclusion. Internal egg qualities like shell weight and haugh unit were significantly increased by FPLE with birds in group with 120ml/litre FPLE having the highest significant values than birds in control and other groups. Haematological results show that for packed cell volume (PCV), Haemoglobin were not similar for all the groups in this experiment. However results for Red blood cell count (RBC) and White blood cell count (WBC) and differential were increased with FPLE intake with birds administered 120ml/litre of FPLE having the highest values for RBC and WBC. Serum chemistry results show similarities for serum total protein, Albumin, Globulin, Total Cholesterol and Serum Alanine Transaminase (SALT). FPLE has been proven to be a haematinic in rats and broiler chickens; this present result further strengthens this assertion though the results for blood analysis are contrary to that obtained by the authors for meat type chickens. It can therefore be concluded that up to 120ml FPLE/litre of drinking water can be tolerated by egg type chickens from point of lay phase to early laying phase.